The Effectiveness of Giving Sauropus Androginus and Carica Papaya to Increase Breast Milk Production in Breastfeeding Mothers - Mega Virgo Septiani; Magdalena Tri Putri; Putri Agus Febriyani (Jurnal Maternitas Kebidanan, 2026)
Breast milk (ASI) is the most complete and ideal source of nutrition for infants, providing all essential nutrients required for optimal growth and development. However, many breastfeeding mothers experience difficulties in milk production, leading to failure in exclusive breastfeeding. One natural approach to enhance breast milk production is through the consumption of Sauropus androgynus (katuk leaves) and Carica papaya (papaya leaves), both known for their lactagogue properties. This study aimed to determine the effectiveness of Sauropus androgynus and Carica papaya in increasing breast milk production among breastfeeding mothers at Kalibunder Public Health Center in 2025. The research employed a qualitative method with a case study design involving two breastfeeding mothers experiencing low milk production. The intervention was conducted for seven days by administering decoctions of 50 grams of katuk leaves and papaya leaves boiled in 300 ml of water, consumed twice daily. The results showed an increase in breast milk volume in both interventions. Sauropus androgynus increased milk volume from 15 ml to 60 ml, while Carica papaya increased it from 20 ml to 60 ml. There was a 5 ml difference between the two interventions, with Carica papaya proving to be more effective in enhancing breast milk production. Therefore, Carica papaya can be considered an effective natural alternative to help breastfeeding mothers improve their milk supply.